KAJIAN TEKNO EKONOMI PAKET TEKNOLOGI BAKTERI PERAKARAN PEMACU PERTUMBUHAN TANAMAN (BP3T) PUPUK KANDANG DAN NANO PESTISIDA SERAI WANGI PADA USAHA TANI KAKAO DI KABUPATEN LIMA PULUH KOTA - Wahyuni, Sri; Rahma, Haliatur; Trisno, Jumsu; Martinius, Martinius; Noveriza, Rita; Reflin; Yuliani, Sri; Nusyirwan, Nusyirwan; Nefri, Jhon (Jurnal AGRISEP, 2020)
Plant Growth Promoting Rhizobacteria (PGPR) plus manure technology is designed to control the vascular streak dieback disease (VSD) which attacks cocoa plants, and improve the plant growth. This research aims to compare the cost of using conventional manure and PGPR plus manure technology. This research was designed in a descriptive quantitative approach using cencus data of 43 people who use PGPR plus manure in Kabupaten Limapuluh Kota. The result shows that the conventional fertilizer costs is more expensive than the PGPR plus manure formula. Therefore, it PGPR plus manure formula is recommended for the cacao farmers in Kabupaten Limapuluh Kota.